2010
DOI: 10.1121/1.3453420
|View full text |Cite
|
Sign up to set email alerts
|

Perception of longitudinal components in piano string vibrations

Abstract: This paper investigates the audibility of longitudinal components in piano string vibrations with listening tests. The recorded fortissimo sounds of two grand and one upright pianos have been resynthesized with and without longitudinal components and used in ABX type listening tests. Results suggest that the longitudinal components are audible up to note C 5 . However, a second test seeking the importance of the difference shows that the effect of longitudinal components for the range A 3 − C 5 is subtle. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…[2][3][4][5] In addition to the recent focus on these complications, research within the past two decades has shown that piano strings vibrate in the longitudinal direction, which produces significant audible effects. 3,6 The origin of these longitudinal vibrations and their relationship to the transverse motion are the subject of the work reported here.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[2][3][4][5] In addition to the recent focus on these complications, research within the past two decades has shown that piano strings vibrate in the longitudinal direction, which produces significant audible effects. 3,6 The origin of these longitudinal vibrations and their relationship to the transverse motion are the subject of the work reported here.…”
Section: Introductionmentioning
confidence: 93%
“…However, questions regarding the origins of longitudinal waves in piano strings remain unanswered. Recent studies indicate that longitudinal waves significantly contribute to the piano sound, 6 but the excitation mechanisms that initiate these waves are still not completely understood. 7 Theoretical work on the longitudinal vibrations in strings dates back to the middle of the last century, 8 and there has been significant progress within the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…While digital waveguides are capable of the highly efficient modeling of linear string behavior, they are not very well suited to model nonlinear string vibration. On the other hand, the nonlinear longitudinal vibrations of the low and middle range of piano strings are very important for realistic bass piano sounds [41]. Because of this need, and by the help of increased computational resources, modal-based academic [17,35,42] and commercial 1 piano models have been developed around year 2005-2006.…”
Section: Modal Synthesis Of String Vibrationsmentioning
confidence: 99%
“…They are, however, not considered of perceptual significance in the three highest octaves (above C5), 3 which is the range where duplex stringing generally is considered most important. Longitudinal modes gain much of their energy from transversal string modes.…”
Section: Introductionmentioning
confidence: 98%